EPIDEMIOLOGICAL SITUATION ON CRIMEAN HEMORRHAGIC FEVER IN THE RUSSIAN FEDERATION IN 2016, AND PROGNOSIS FOR 2017 - A. S. Volynkina; E. S. Kotenev; Ya. V. Lisitskaya; O. V. Maletskaya; L. I. Shaposhnikova; A. N. Kulichenko (Проблемы особо опасных инфекций, 2017)
Abstract. This paper presents analysis of epidemiological situation on Crimean hemorrhagic fever (CHF) in Russia in 2016. Summarized are the results of epizootiological survey of the territory of the natural CHF focus in the south of the European part of Russia, discussed are the results of genetic typing of CCHFV RNA isolates. In 2016, the Russian Federation reported 162 cases of CHF. Increase in the incidence of CHF occurred in the Astrakhan, Volgograd Regions, Republic of Kalmykia, and Stavropol Territory. For the first time CHF case was identified in Kabardino-Balkar Republic. In 2016 in stationary points for the long-term observation of the natural CHF focus, high abundance rates of larvae and nymphs of H. marginatum remain. In case of successful Ixodidae ticks wintering and late onset of the hot and dry season in the summer, 2017, there is probability that high numbers of H. marginatum will be retained and the period of the imago activity is prolonged, which may in its turn  contribute to the increase in CHF morbidity rates.